Efektivitas Alokasi Anggaran Biaya Operasional Perkantoran (BOP) pada Kantor Urusan Agama Kabupaten Sidenreng Rappang - Rustan, Rustan; S, Muliani; Nilwana, Andi; Jamaluddin, Jamaluddin; Rais, Muhammad; K, Nuraini (PUBLICNESS: Journal of Public Administration Studies, 2025)
This research analyzes the effectiveness of Office Operating Costs (BoP) allocation at the Office of Religious Affairs (KUA) in Sidenreng Rappang Regency, South Sulawesi. Using a quantitative descriptive approach, this study focuses on budget management, financial planning, funding allocation effectiveness, and identification of implementation barriers. Data was collected through in-depth interviews, document analysis, and direct observation, then analyzed using data reduction techniques, data presentation, and conclusion drawing. The results reveal that BoP allocation effectiveness still faces significant challenges, including limited employee participation in the budget planning process, disproportionate fund allocation relative to operational needs, and disbursement delays that impede public service continuity. The main inhibiting factors include minimal management transparency, limited human resource competencies in financial administration, and policy inconsistencies causing budget instability. This research recommends reforms to the fund disbursement system, increased budget transparency, and human resource capacity development to enhance BoP management effectiveness and optimize KUA services in Sidenreng Rappang Regency.